Cheering Enhances Inter‐Brain Synchronization Between Sensorimotor Areas of Player and Observer1. (3rd July 2018) - Koide, Tadayoshi; Shimada, Sotaro
Abstract: Cheering for another person is a common experience. Cheering may facilitate the cheerer's subjective unity with the cheered‐for person, potentially involving synchronized activity between the two individuals' brains. In the current study, we measured the sensorimotor cortical activity of a player and an observer simultaneously during a competitive game, using functional near‐infrared spectroscopy. The player performed the rock‐paper‐scissors game against an experimenter while the observer either cheered for that player (cheering group) or judged whether the player cheated or not (control group). In the cheering group, observers reported a significantly stronger sense of unity with the player, and exhibited greater sensorimotor activation when observing the player win, compared with the control group. The functional connectivity between the sensorimotor areas of the player and observer was significantly greater in the cheering group, exhibiting a significant correlation with the subjective sense of unity between the player and observer. These results suggest that cheering enhances the synchronization of the player's and the observer's internal states, establishing a sense of unity.